Elites and Economic Development Comparative Studies on the Political Economy of Latin American Cities - Walton, John (University of Texas Press, 2021)
This book is a detailed comparative analysis of development politics in four urban regions of Latin America, two in Mexico and two in Colombia. John Walton has based his studies on the assumption that the problems of economic growth are essentially political, that is, are problems of choice, decision-making, and the exercise of power. His fundamental purpose has been to discover how elites of different kinds are more and less successful in the promotion of economic development, which he defines as a process in the organization of a society leading not only to higher levels of efficient output but also to a more equitable distribution of benefits. At the time, the four cities compared were the second- and third-largest metropolitan areas in each country, Guadalajara and Monterrey in Mexico, Medellín and Cali in Colombia.